Detection of Powdery Mildew Resistance Gene in Melon Cultivar Meloni Based on SCAR Markers - Muhammad Alif Ishak; Budi Setiadi Daryono (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2020)
Powdery mildew is one of the diseases caused by fungal infections that can reduce the production of melon fruit worldwide including in Indonesia. A powdery mildew-resistant cultivar of melon is needed to increase melon yield crops. This study aimed to detect resistance gene linked to powdery mildew using a sequence characterized amplified region (SCAR) markers. The melon cultivar Meloni was used in this study. SL-3, PI 371795, and Aramis cultivar were used to compare. Amplification of the marker was performed employing a pair of primers. The result showed that Meloni had a powdery mildew resistance gene by the presence of a DNA target band at 1058 base pair (bp). Based on this result, it could be concluded that Meloni was an excellent melon cultivar because of its ability to overcome the powdery mildew infections naturally. SCAR markers have been used for various purposes, especially to detect resistance genes to plant diseases. The present study had provided information for plant breeders about Meloni as the new melon cultivar that was genetically resistant against powdery mildew infections. Furthermore, Meloni could be proposed as an alternative to native Indonesian superior melon seeds.